LGBT Representation in Johny Johny Yes Papas Lellobee City Farm Animation: A Narrative Analysis of Branston and Stafford's Perspective (Jurnal Kopis: Kajian Penelitian dan Pemikiran Komunikasi Penyiaran Islam, 2024)
Johny Johny Yes Papas animation is one of the Lellobee City Farm animations produced by Moonbug, a global entertainment company based in London and Los Angeles. The animation represents an LGBT family that is well accepted in the social environment. This research aims to analyze the animation from a narrative perspective. This research uses a descriptive qualitative approach and constructivism paradigm, with Branston and Stafford's common narrative model to analyze the data. The results of this study show that there are four different codes that reveal the LGBT narrative. Namely, the action code that shows the role of father and mother of the dad and papa characters; the cultural code is the dad and papa characters wearing a wedding ring as the culture adopted, one of the signs of love bonding is by wearing a ring, a graceful gesture and a rosy blush on the papa character; Symbolic code is the same ring on the ring finger of the dad and papa characters which shows that both are a couple bound in a sacred bond; Semic code appears in the background and setting of the story in a house which shows that this animation tells a family, as well as characterizations and characters of the three characters who display the characters and roles of fathers, mothers, and children in a family.